Nursing - Ulutasdemir, Nilgun (IntechOpen, 2018)
This book covers topics from nursing history and philosophy, communication and ethics in nursing, nursingand culture. Thus, it can be used as a guide by student nurses and working nurses to recognize the nursing profession and to keep up with current developments. In this book, you will find all aspects of nursing profession.